Enhanced Photoelectrochemical Performance in Reduced Graphene Oxide/BiFeO3 Heterostructures. Issue 16 (9th February 2017) - Ren, Yan; Nan, Feng; You, Lu; Zhou, Yang; Wang, Yanyan; Wang, Junling; Su, Xiaodong; Shen, Mingrong; Fang, Liang
Abstract : BiFeO3 (BFO)‐based ferroelectrics have been proved to be visible‐light‐driven photoelectrodes for O2 production. However, the hitherto reported photoelectrochemical performances remain inferior to meet the requirements for any applications. Besides, expensive noble metals (Ag, Au) are commonly required to achieve high photoelectric conversion efficiency. Here, the significant enhancements of photoelectrochemical performance is reported by fabricating a noble‐metal‐free reduced graphene oxide (RGO)/BFO composite film via a simple and cost‐effective solution process. The optimized RGO/BFO composite film exhibits a 600% improvement of the short‐circuit photocurrent density compared to that of the pristine BFO, and also outperforms the noble‐metal/BFO cells under the same reaction conditions. Furthermore, the incident photon‐to‐current efficiency of the optimized RGO/BFO sample shows threefold enhancement. This study delivers a facile and low‐cost approach to preparing 2D materials/ferroelectric heterostructures and offers a promising pathway to boost the performance of semiconducting ferroelectric photoelectrodes. Abstract : Reduced graphene oxide (RGO)/BiFeO3 composite is successfully prepared by the sol–gel method followed by the dip‐coating method. The RGO can significantly suppress the recombination of the photogenerated carriers in the BiFeO3 film due to its delocalized conjugated structure and superior electrical conductivity, which lead to the enhanced incident photon‐to‐current efficiency and photocurrent density in the optimized RGO/BiFeO3 composite system.